2017
DOI: 10.1007/s11920-017-0840-4
|View full text |Cite
|
Sign up to set email alerts
|

A Network-Based Neurobiological Model of PTSD: Evidence From Structural and Functional Neuroimaging Studies

Abstract: Purpose of Review Although a fine-grained understanding of the neurobiology of posttraumatic stress disorder (PTSD) is yet to be elucidated, the last two decades have seen a rapid growth in the study of PTSD using neuroimaging techniques. The current review summarizes important findings from functional and structural neuroimaging studies of PTSD, by primarily focusing on their relevance towards an emerging network-based neurobiological model of the disorder. Recent Findings PTSD may be characterized by a wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
263
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(312 citation statements)
references
References 83 publications
21
263
1
1
Order By: Relevance
“…Moreover, associations have been reported between CAB integrity and functioning in episodic memory, decision-making, and executive control [42,43]. The CAB has also been shown to directly connect the posterior cingulate cortex and the subiculum of the hippocampus [44], both of which are critical nodes in the default mode network shown to be altered in PTSD [1,45]. The CAB connects the hippocampus and other regions of the medial temporal lobe with the posterior cingulate [43], an area that has been shown to exhibit alterations of gray matter integrity (thinning) in this group of participants [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, associations have been reported between CAB integrity and functioning in episodic memory, decision-making, and executive control [42,43]. The CAB has also been shown to directly connect the posterior cingulate cortex and the subiculum of the hippocampus [44], both of which are critical nodes in the default mode network shown to be altered in PTSD [1,45]. The CAB connects the hippocampus and other regions of the medial temporal lobe with the posterior cingulate [43], an area that has been shown to exhibit alterations of gray matter integrity (thinning) in this group of participants [30].…”
Section: Discussionmentioning
confidence: 99%
“…Despite decades of psychiatric research, a comprehensive understanding of the network disruptions [1] predisposing and underlying posttraumatic stress disorder (PTSD) is still emerging [2,3]. While the majority of neuroimaging investigations have focused on structural [4] and functional [5] aspects of PTSD, there is a growing body of literature regarding white matter integrity related to the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…For an in depth discussion of this topic in adult PTSD, I refer readers elsewhere in this special issue [17]. Briefly, numerous studies have identified a set of core, functionally connected networks in the brain.…”
Section: Large Scale Network Abnormalities In Pediatric Ptsdmentioning
confidence: 99%
“…In addition to the frontolimbic model, recent work also implicates dysfunction in larger scale brain networks in adult PTSD involved in salience detection, self-referential thought, and executive control. A more in depth discussion of these network abnormalities can found be found elsewhere in this special issue [17], though I briefly discuss relevant findings in pediatric PTSD later in this article.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the fronto-limbic circuitry, aberrations between and within (Sripada et al, 2012) the default mode network (DMN), salience network (SN), and the central executive network (CEN) were demonstrated in PTSD. The DMN and CEN were found to be weakly interconnected and hypoactive, hypothetically destabilized by an overactive and hyper-connected SN and a low saliency perception threshold, along with inefficient DMN-CEN modulation (Akiki, Averill, & Abdallah, 2017). Abnormalities within the CEN may underlie some of the cognitive, executive, and emotional regulatory dysfunctions in PTSD (Lanius, Frewen, Tursich, Jetly, & McKinnon, 2015).…”
Section: Introductionmentioning
confidence: 99%